Janice VanCleave's A+ projects in earth science : winning experiments for science fairs and extra credit. - VanCleave, Janice Pratt (New York : John Wiley, 1999)
Presents thirty sample science projects as well as ideas for small changes to the original experiments thereby encouraging creativity and increased learning.
Includes index.
Also available as an electronic book via the World Wide Web to institutions affiliated with netLibrary, Inc.
Keywords: Earth sciences -- Experiments -- Juvenile literature; Science projects -- Juvenile literature; Earth sciences -- Experiments; Science projects; Experiments